(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
On May 11, 2017, the President of Uzbekistan Shavkat Mirziyoyev signed a decree “On the creation of the State Committee of the Republic of Uzbekistan for Forestry.” The State Forestry Committee is part of the Cabinet of Ministers complex for agriculture, processing of forestry products and consumer goods. The main objectives and areas of activity of the State Committee of the Republic of Uzbekistan for Forestry are mainly the implementation of a unified state policy in the field of forestry, aimed at the comprehensive expansion and rational use of forest resources.